O uso das HQ’s como recurso didático para a formação do conceito de cultura - Souza, Maria de Fátima Costa (2010)
The studies accomplished on comic strips are growing every day. This progress is a reflex of the effectiveness of that visual resource. In the education, the comic strips (HQ's) can be used to reach many objectives. Besides entertaining, this literary gender can supply elements for analysis, interpretation and critical reflection of the readers. The objective of this research is to know the potential of HQ's a didactic resource to the classroom. For this we used the concept of Brazilian Northeastern culture, starting from the graphic representation of the typical elements of our country like clothing, language, religiosity, feasts and musicality in the little strips of the Xaxado´s Group. We have built a conceptual picture involving the concepts of comic strips, didactic resources, culture and Northeast region. For the collection of data, we analyzed how elements of the Northeastern culture were represented in the little strips of the Xaxado’s group. After, we applied a questionnaire to a group of 36 students of the 4th series of the Teaching Fundamental I, of a public school of teaching and we accomplished an intervention in this group, for six days, applying a didactic sequence properly structured to form a concept of culture in the students. The results indicate that the comic strips can be used as didactic resources.